Analisis Implementasi Enterprise Resource Planning Pada Human Resource Management (Studi Kasus: PT. Bengawantex) - Aziz Jihadian Barid; Eko Sediyono; Aris Puji Widodo (STMIK Banjarbaru, 2023)
This study aims to analyze the implementation of Enterprise Resource Planning (ERP) in order to find out how much influence its implementation has on the Human Resources management of PT. Bengawantex. Research using quantitative methods with a simple regression approach. This method is used to predict the effect of the dependent variable (human resource management) based on the independent variable (enterprise resource planning). The results of simple linear regression calculations show a value of 0.398. This value means that the influence of Enterprise Resource Planning (X1) on Human Resource Management (Y) is 39.8%. The remaining 60.2% is influenced by other variables outside the model, namely the t-count of variable X (product quality) of 1.408 which is smaller than the t-table value (2.015), and a significance value of 0.254 (smaller than the significance value set at 0.05). The t-count value which shows a positive number means that company resource planning (variable X) has no significant effect on human resource management (variable Y).Keywords: Enterprise Resource Planning; Human Resource Management; Linear regression AbstrakPenelitian ini bertujuan untuk menganalisis implementasi Enterprise Resource Planning (ERP) guna mengetahui seberapa besar pengaruh penerapannya terhadap manajemen Sumber Daya Manusia PT. Bengawantex. Penelitian menggunakan metode kuantitatif dengan pendekatan regresi sederhana. Metode ini digunakan untuk memprediksi pengaruh variabel dependen (manajemen sumber daya manusia) berdasarkan variabel independen (Enterprise Resource Planning). Hasil perhitungan regresi linier sederhana menunjukkan nilai sebesar 0,398. Nilai ini berarti pengaruh Enterprise Resource Planning (X1) terhadap Manajemen Sumber Daya Manusia (Y) adalah 39,8%. Sisanya 60,2% dipengaruhi oleh variabel lain di luar model, yaitu t-hitung variabel X (kualitas produk) sebesar 1,408 lebih kecil dari nilai t-tabel (2,015), serta nilai signifikansi sebesar 0,254 (lebih kecil dari nilai signifikansi yang ditetapkan sebesar 0,05). Nilai t-hitung yang menunjukkan angka positif berarti perencanaan sumber daya perusahaan (variabel X) tidak berpengaruh signifikan terhadap pengelolaan sumber daya manusia (variabel Y).